A personal touch: Text messaging for loan repayment - Dean Karlan; Melanie Morten; Jonathan Zinman (Yale University, Economic Growth Center, 2012)
We worked with two microlenders to test impacts of randomly assigned reminders for loan repayments in the text messaging capital of the world. We do not find strong evidence that loss versus gain framing or messaging timing matter. Messages only robustly improve repayment when they include the loan officer's name. This effect holds for clients serviced by the loan officer previously but not for first-time borrowers. Taken together, the results highlight the potential and limits of communications technology for mitigating moral hazard, and suggest that personal obligation/reciprocity between borrowers and bank employees can be harnessed to help overcome market failures.
Keywords: D21; D92; G21; O16; O17; 330; microcredit; microfinance; randomized evaluation; development finance